DIGITAL TRANSFORMATION THROUGH LEARNING MANAGEMENT SYSTEM IMPLEMENTATION IN SECONDARY SCHOOLS: ANALYSIS OF IMPACT, CHALLENGES, AND ADAPTATION STRATEGIES - Nirsal, Nirsal (PT. Hafasy Dwi Nawasena, 2025)
Digital transformation in the secondary education sector has experienced significant acceleration with the adoption of Learning Management Systems (LMS) as the primary digital learning platform. This research aims to analyze the impact of LMS implementation, identify challenges faced, and explore effective adaptation strategies in secondary schools. The study employs a qualitative approach with document analysis and case studies from various LMS implementations in secondary schools in Indonesia and other countries. Data was collected through in-depth analysis of 25 previous studies discussing LMS implementation in secondary education contexts. Research findings indicate that LMS implementation provides significant positive impacts on improving teacher-student interaction, learning access flexibility, school management efficiency, and learning personalization. However, implementation faces major challenges including technological infrastructure limitations, digital literacy gaps, resistance to change, and budget constraints. Effective adaptation strategies include continuous teacher training, technological infrastructure strengthening, clear institutional policy development, and hybrid learning model adoption. AI technology integration in LMS and development of locally-based platforms emerge as current innovation trends. The research concludes that successful digital transformation through LMS requires a holistic approach integrating technology, pedagogy, and management aspects with comprehensive policy support.